The setpoint diet : the 21-day program to permanently change what your body "wants" to weigh - Bailor, Jonathan (Hachette Books, 2018)
Your body fights to keep you within a range of about 15 pounds--also known as your "setpoint weight." New research reveals that you can lower your setpoint and end that battle for good by focusing on the quality of calories you eat, not the quantity. With The Setpoint Diet, you will reprogram your body with a 21-day plan to rev up your metabolism, eliminate inflammation, heal your hormones, repair your gut, and get your body working like that of a naturally thin person--permanently. The Setpoint Diet is a lower-carb menu that focuses on specific anti-inflammatory whole foods, including tons of produce, nutritious proteins, and therapeutic fats. Its creator, Jonathan Bailor, founded SANESolution, a weight loss company that has reached millions of people. Proven to help you lose weight naturally and maintain it, The Setpoint Diet is your new blueprint for healthy living.